Violent Extremism and its Continuum - Gunaratna, Rohan (2018)
ISIS may have suffered battlefield reverses, but in some respects – not least ideologically – it is resilient. Analysts, academics and security officials should resist the impulse to call time on the study of these types of issues – this mistake has been made before.